ORGANISASI MAPALUS DALAM PELAKSANAAN PEMBANGUNAN DI DESA KALEOSAN - KOMBAITAN, YESICHA; POSUMAH, JOHNNY HANNY; TAMPI, GUSTAAF BUDDY (JURNAL ADMINISTRASI PUBLIK, 2019)
The mapalus system in implementing development in the village has begun to disappear. And the main cause is all because of technological developments so that the people who have started to forget the mapalus culture that has been valid in the village has become a tradition in the village. The purpose of this study is to find out how mapalus organizations are in implementing development in the village. This study uses descriptive qualitative research methods. Data collection techniques used are observation, interviews and data collection with documents. To see how the mapalus organization is carrying out development in the village of Kaleosan. The researcher uses three indicators, namely: Planning and setting goals, providing services and monitoring from the government. Based on the results of this study stated that the role of the community and even the mapalus organization in the village in the implementation of development in the village is still very lacking because the community that along with technological development has begun to forget the habits of mapalus. mapalus in development. It can be concluded that the mapalus organization in the implementation of development in Kaleosan village is still not good. Keywords: Mapalus ,Organization, Village Development